Developing alternative methodological framework for facilitating adult learning: the outcome of an experiment (2016)
This paper presents the outcome of an experiment on an alternative method of facilitating adult learning called DISSAAP. It is an acronym where D stands for Discussion of learning content, I for identification of Deductions, S for Summation of recurring major deductions, S for synthesis of deductions in order of importance, A for Agreement of synthesis, A for Adoption of the synthesis, and P for Presentation. This approach was experimented with a group of adult learners participating in a University Distance Learning Programme with the concept of motivation as the course content Learners were allowed to discuss individually what could motivate them to achieve effective learning. From the discussion, deductions made by them were identified. The major recurring deductions were recognised and summed up for synthesis which were, thereafter, arranged in their order of importance. In collaboration with the facilitators, agreement of the synthesis was reached with the learners for adoption of what motivate adult learners. The adoption led to the presentation of the new knowledge on motivation of adult learners for general acceptability by the learners. Findings of the experiments show that learners' intuitive capacity, power, and empowerment to arrive at knowledge themselves were greatly enhanced which led to active participation of the learners in the teaching and learning process. The experiment proved that "DISSAAP" is an effective methodological approach for facilitating adult learning and is, therefore, recommended for adult educators and facilitators